Risk factors of necrotizing enterocolitis among neonates admitted to the neonatal intensive care unit at the selected public hospitals in southern Ethiopia, 2023 - Abebe, Mesfin; Ayehu, Mequanint; Tebeje, Tsion Mulat; Melaku, Getnet (Frontiers in Pediatrics, 2024)
Necrotizing enterocolitis is a serious intestinal condition characterized by ischemic necrosis of the intestinal mucosa, inflammation, and invasion by gas-forming organisms, posing a significant threat to neonatal health. Necrotizing enterocolitis is still a major cause of neonatal morbidity and mortality, especially in developing countries. since little research has been done in Ethiopia and the study area regarding the risk factors for necrotizing enterocolitis. Therefore, the goal of this study was to fill the aforementioned gap.Objective: To identify the risk factors of necrotizing enterocolitis among neonates admitted to the neonatal intensive care unit at selected general and referral hospitals of Southern Ethiopia, 2023 Methods and materials: A facility-based unmatched case-control study was carried out. All neonates admitted to the neonatal intensive care unit and diagnosed with necrotizing enterocolitis by the attending physician during the data collection period were considered cases, whereas neonates admitted to the neonatal intensive care unit but not diagnosed with necrotizing enterocolitis during the data collection period were considered controls. Data were collected through face-to-face interviews as well as record reviews using the Kobo toolbox platform. The binary logistic regression method was used to determine the relationship between a dependent variable and independent variables. Finally, a p-value of <0.05 was considered statistically significant.: This study included 111 cases and 332 controls. Normal BMI[AOR = 0.11, 95% CI: (0.02, 0.58)], history of khat chewing [AOR = 4.21, 95% CI: (1.96, 9.06)], term gestation [AOR = 0.06, 95% CI: (0.01, 0.18)], history of cigarette smoking [AOR = 2.86, 95% CI: (1.14, 7.14)], length of hospital stay [AOR = 3.3, 95% CI: (1.43, 7.67)], and premature rupture of membrane [AOR = 3.51, 95% CI: (1.77, 6.98)) were significantly associated with NEC.In this study body mass index, history of khat chewing, gestational age, history of cigarette smoking, length of hospital stays, and premature rupture of membrane were found as risk factors for necrotizing enterocolitis. Therefore, healthcare providers should be aware of these risk factors to identify high-risk newborns and take preventive actions.